Pengembangan Multimedia Pembelajaran Interaktif Menggunakan Aplikasi Articulate Storyline - Muhammad Syahrul; Fetri Yeni J (Universitas Negeri Padang, 2023)
The purpose of this study id to find out how to develop interactive learning multimedia using the articulate storyline application, to find out the validity and practicality of interactive learning multimedia in class VIII at indonesian subject at MTsN 6 Padang. The results of the material validity test are in the